PERAN KOMISI PEMILIHAN UMUM (KPU) DALAM MENJAGA DEMOKRASI: TINJAUAN TERHADAP PELAKSANAAN DAN TANTANGAN PEMILU DI KOTA PEMATANG SIANTAR - Haykal M Raihan; Kristiani Pasaribu; Peninna Simanjuntak; Vanesia Amelia Sebayang (Bajang Institute, 2024)
This paper aims to analyze the roles and challenges faced by the Pematang Siantar General Election Commission (KPU) from 2019 to 2024. In 2019, the Pematang Siantar KPU prepared for the general elections to be held in 2020. However, challenges arose when the Covid-19 outbreak hit in 2020, hampering various activities of the Pematang Siantar KPU. Another challenge arose in 2021 when one of the election winners, Mr. Asner, passed away. Despite facing many challenges, the Pematang Siantar KPU has made innovations in carrying out its duties. In the following years, the situation began to be controlled, especially in 2022-2023, where the Pematang Siantar KPU returned to its normal duties to prepare for the 2024 elections. The roles and challenges faced by the Pematang Siantar KPU during the 2019-2024 period will be the main focus of this paper. The research method used is the historical method with four stages. First, data collection is done through digital news and oral interviews. Second, the data is verified for authenticity and credibility. Third, the data were combined to be analyzed from 2019 to 2024. Finally, the results of the analysis are presented in a paper that highlights the different roles and challenges faced by the Pematang Siantar KPU, especially in critical years such as 2020 and 2021